2017
DOI: 10.1039/c7ra06659g
|View full text |Cite
|
Sign up to set email alerts
|

Zinc dopant inspired enhancement of electron injection for CuInS2quantum dot-sensitized solar cells

Abstract: The PCE of doped CuInS2QDSCs increased from 5.21% to 5.90%, due to broadened optoelectronic response range and accelerated electron injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The Zn doping into the cores was also supported by the blue shifts observed in the absorption and PL spectra in Figure S3. Previous studies have reported that Zn doping reduces internal core defects and increases PL intensities. , ,, Thus, verification of the diffusion behavior of Zn atoms is informative for revealing the origins of temperature-dependent optical properties.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The Zn doping into the cores was also supported by the blue shifts observed in the absorption and PL spectra in Figure S3. Previous studies have reported that Zn doping reduces internal core defects and increases PL intensities. , ,, Thus, verification of the diffusion behavior of Zn atoms is informative for revealing the origins of temperature-dependent optical properties.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies have reported that Zn doping reduces internal core defects and increases PL intensities. 18,[21][22][23]25,26 Thus, verification of the diffusion behavior of Zn atoms is informative for revealing the origins of temperature-dependent optical properties. Verification of the Zn Diffusion Behavior from the ZnS Shell to the CISe Core.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…also demonstrated that after being doped with Zn, CuInS 2 quantum dots exhibit benign electronic properties. The rate constant of electron transfer from CIZS QDs to TiO 2 nanoparticles is greater than that of pure CuInS 2 QDs by an order of magnitude, which ultimately results in an enhanced power conversion efficiency of solar cells …”
Section: Introductionmentioning
confidence: 99%
“…However, there is no report on the advantages of zinc in CuInS 2 solar cells. Recently, Wu et al [26] reported fabrication of zinc doped CuInS 2 quantum dot-sensitized solar cells under air circumstance. After being doped with zinc, CuInS 2 quantum dots (QDs) exhibited desired tunable optical and electronic properties, more specifically, photoluminescence (PL) emission and band gap.…”
Section: Introductionmentioning
confidence: 99%